Feminism and Gender Equality among Orang Asli Women: Implications for Customs and Laws - Abd Karim, Rafidah; Mustapha, Ramlee; Abd Wahab, Norwaliza; Aliasak, Mohd Hasrol Hafizz; Che Ghani, Nurul Farhani; Irwansyah, Irwansyah (Faculty of Law, Hasanuddin University, 2025)
Although Malaysia has made progress in recognising Indigenous rights, the perspectives of Orang Asli women on feminism and gender equality remain largely absent from legal and academic discourse. This article examines the legal tensions between indigenous customary laws and Malaysia’s constitutional commitment to gender equality, as perceived and experienced by Orang Asli women. The central legal issue explored is whether customary practices that reflect patriarchal norms can withstand constitutional scrutiny under Article 8 of the Federal Constitution, and how these practices align with Malaysia’s obligations under CEDAW and UNDRIP. Using a doctrinal legal methodology, the study systematically examines constitutional provisions, relevant legislation, and judicial interpretations concerning indigenous law and gender rights. A socio-legal component complements this analysis through empirical data collected from 120 questionnaires and 30 semi-structured interviews with Orang Asli women from five selected tribes, providing context to how these legal norms function in practice. This article contributes to legal theory by engaging with legal pluralism and feminist legal thought, revealing how unregulated customary practices can undermine fundamental rights. Thus, it enhances legal studies by highlighting an ethical framework for legislative and judicial reconciliation between constitutional equality and indigenous legal traditions. In a pluralistic legal circumstance, this study advocates on Malaysian legal institutions to acknowledge the changing voices of Indigenous women as catalysts of change.